(untitled) (Research, Society and Development, 2023)
Orthodontic appliances fixed and mobile are used for the treatment of malocclusion, dental corrections, problems in arch development and growth and for aesthetic reasons. Therapies performed with these devices can affect the oral microbiota resulting in a series of effects on oral health. There is a large discrepancy when we compare the types of appliances and their implications on the oral microbiota, with fixed appliances being the ones that affect the most, by the difficulty of cleaning they provide and by the bigger force exerted on the periodontium. This literature review aims to detail the secondary effects of the use of orthodontic appliances in the constitution of the oral microbial community. This is a descriptive bibliographic study of the narrative review type. Using the descriptors "Orthodontic Appliances, Fixed", "Orthodontics", "Microbiota" and "Periodontal Diseases", a search was performed on the digital platforms VHL, Capes, SciELO and PubMed using the Boolean operators “AND” and “OR”. From a total of 31 works 6, 29 were selected in Portuguese, English and Spanish, dating between 2014 and 2022. It was found that by the difficulty in cleaning and the greater force exerted on the periodontium results in changes in the growth rate of certain species of bacteria and fungi, being variable according to the time of use, presence of biofilm, development of caries and involvement of periodontal diseases.